Development of a Shopping Well-Being Model for Purchasing Jambi Batik Products - Sari, Novita; Rosyid, Garry Yuesa; Perdana Siregar, Ade (Dinasti Publisher, 2025)
A person's behavior in online shopping tends to be hodonistic, which is influenced by one factor, namely hedonic motives. Purchases made online include considerations that refer to the experiences of other consumers after making the transaction. The hedonic behavior of consumers in purchasing a product, especially Jambi Batik products, can consider the role of shopping well-being so that consumers can make continuous purchases. The aims of this research are (1) To examine the influence of hedonic behavior on continuous purchase intention (2) To examine the influence of hedonic behavior on shopping well-being (3) To examine the influence of shopping well-being on continuous purchase intention (4) To examine the role of shopping well-being -being is able to mediate the influence of hedonic behavior on continuous purchase intention. The data analysis method used is Structural Equation Modeling (SEM) measurements using SmartPLS software. The results of the research are that hedonic behavior has a positive effect on continuous purchase intention, hedonic behavior has a positive effect on shopping well-being, shopping well-being has a positive effect on continuous purchase intention, shopping well-being is able to play a positive role as a mediating influence of hedonic behavior on continuous purchase intention.